PERAN DAN KONTRIBUSI ILMU KALIGRAFI DALAM DUNIA ISLAM - Nurul Huda Hasibuan; Putri Ani Dalimunthe (Yayasan Haiah Nusratul Islam, 2024)
Calligraphy, one of the Islamic arts, has gotten a great attention in Muslim community. Basically, calligraphy is artistic writings (khat) taken from Al Quran and it is named based on the place: Makki, Madani, Anbari and Baghdadi. By the time, names of (khat) shown, seems like Khufi, Mutsallats, Mudawwar, and some other types of writing. Calligraphy has a big role in developing Islamic civilization in the world. The influence of Islamic power expantions, Arabitation, the role of the King and social elites give motivation and facilitate the development of calligraphy and influent the development of science especially in Abbasiyah period. After the Abbasiyah period, the existence of calligraphy still was existing, developing and showing the phenomenal calligrafers like Ibnu Muqlah.